2008
DOI: 10.1080/03768350701836145
|View full text |Cite
|
Sign up to set email alerts
|

Affordable and middle-class housing on Johannesburg's mining sites: a cost–benefit analysis

Abstract: This paper examines the redevelopment of former gold mining land close to the downtown area of Johannesburg for affordable and middle-income housing. This could provide savings for out-ofpocket costs, time saving for commuting costs and better property appreciation. However, the properties may be costly to remediate and may still pose some health risks from exposure to radon. A cost -benefit analysis examined these issues from the perspective of the home occupant. The present value of the net benefits over a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…There are ethical debates about the level of risk in living on mine residue areas. A mid-2000s study found that a sample group was willing to take such risks in return for proximity to the city (Simons & Aly, 2008). The City of Ekurhuleni embarked on a feasibility study into the possibility of residential development on their extensive mining-affected land.…”
Section: Photograph By Clive Hassallmentioning
confidence: 99%
“…There are ethical debates about the level of risk in living on mine residue areas. A mid-2000s study found that a sample group was willing to take such risks in return for proximity to the city (Simons & Aly, 2008). The City of Ekurhuleni embarked on a feasibility study into the possibility of residential development on their extensive mining-affected land.…”
Section: Photograph By Clive Hassallmentioning
confidence: 99%
“…The redevelopment of contaminated properties has received attention in all regions of the world (e.g., Cao and Guan, 2007;Miyagawa and Nakayama, 2001;Newton, 2010;Simons and Karam, 2008;Thornton et al, 2007;Turvani, 2010;Yacovone, 2011), a product both of interest in revitalizing underperforming, previously developed land and of concern over environmental distress. Because these so-called brownfields may pose threats to public health and the environment and depress the economy of local neighborhoods, as well as provide potential opportunities for densifying and combating sprawl, their redevelopment mixes elements of contemporary practice in development and environmental protection.…”
Section: Introductionmentioning
confidence: 99%
“…The presence and vast distribution of uranium and its decay products from tailings constitute a significant source of environmental radiation [4,5] which has the potential to fractionally elevate public exposure beyond recommended levels. Hence, it is plausible to believe that some South African gold mines have contributed either directly or indirectly to uranium pollution and radioactivity elevation, including radon concentrations in areas near uranium producing mines [6,7].…”
Section: Introductionmentioning
confidence: 99%